Insufficient Plasma Melatonin and Its Association With Neuropsychiatric Impairments in Patients With T2DM - Shuai He; Yue Yu; Peng-quan Chen; Hui-min Sun; Xin-ran Gao; Huai-zhi Sun; Jin-fang Ge (Journal of Diabetes Research)
Conclusion: MLT levels decreased in patients with T2DM and were associated with neuropsychiatric impairments and inflammatory status, and MLT might be developed as a therapeutic agent and predictive indicator for T2DM-associated executive impairment and depression status.